Profesionalisme Guru PAI Dalam Memanfaatkan Teknologi Informasi Dan Komunikasi (Studi Kasus SMA Negeri 1 Kutorejo Mojokerto) - Amru Almu'tasim (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2021)
Teacher professionalism is a qualified, competent, and committed professional teacher who is devoted to education. Information and Communication Technology is electronics that consists of hardware and software. Based on the results of data analysis, it can be seen that: 1) The professionalism of Islamic Religious Education Teachers in SMA Negeri 1 Kutorejo Mojokerto is maximal, teachers teach according to their fields, teachers understand structures, concepts, and scientific mindsets that support broad and deep subjects. 2) Teachers of Islamic Religious Education in Utilizing Information and Communication Technology at SMA Negeri 1 Kutorejo Mojokerto have made good use of them, especially teachers of Islamic religious education. The use of information and communication technology is considered to be very helpful for students in the learning process.